GW26-e5449 Left Ventricular transmural strain gradient analysis by Layer-specific Strain Imaging - Yu, Chao; Ding, Qian; Jin, Wenying; Wu, Peihua; Li, Xin; Liu, Dongyue; Zhu, Tiangang (Journal of the American College of Cardiology, 2015)
Usinglayer-specific strain imaging, peak longitudinal strain (PLS) and peak circumferential strain (PCS) of all three layers' myocardium were measured in the three groups Thirty-eight healthy subjects, thirty-three patients with cardiovascular risk factors whose coronary angiogram is negative () and twenty-seven patients with heart failure were enrolled in this study.